2009
DOI: 10.1089/sur.2008.011
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphonuclear Neutrophil Infiltration Intensity as Consequence ofEntamoeba histolyticaDensity in Amebic Colitis

Abstract: Neutrophils and lymphocytes, particularly the former, are associated significantly with the density of parasites. Our findings support the theory that PMN interaction with E. histolytica contributes to the pathogenesis of amebic intestinal lesions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 31 publications
0
17
0
Order By: Relevance
“…The causative protozoan parasite, E. histolytica (Figure 1), is a potent pathogen, transmitted via ingestion of the cystic mature form (Figure 2), the infective stage of this protozoan parasite (Dickson-Gonzalez, et al 2009). Fig.…”
Section: Pathologymentioning
confidence: 99%
See 2 more Smart Citations
“…The causative protozoan parasite, E. histolytica (Figure 1), is a potent pathogen, transmitted via ingestion of the cystic mature form (Figure 2), the infective stage of this protozoan parasite (Dickson-Gonzalez, et al 2009). Fig.…”
Section: Pathologymentioning
confidence: 99%
“…1. Entamoeba histolytica throphozoites, showing nucleus and karyosoma (arrow) (HF, 1000X) (Dickson-Gonzalez et al, 2009) Viable in the environment for weeks to even months, cysts can be found in fecally contaminated soil, fertilizer, or water or on the contaminated hands of food handlers and contaminated elements that can be used during food preparation or ingestion (DicksonGonzalez, et al 2009).…”
Section: Pathologymentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, several reports suggest that neutrophils play a protective role in amoebiasis . However, other reports indicate that trophozoites making direct contact with neutrophils provoke lysis of these leukocytes, resulting in the release of their lytic enzymes, which in turn provoke tissue damage . Therefore, the interaction of neutrophils with this parasite is complex and not completely understood.…”
Section: Introductionmentioning
confidence: 99%
“…Neutrophils are infiltrated in the inflammatory site at early stages of amebiasis [4]. Even though some studies in mice reported that neutrophils are not important to eliminate E. histolytica infection from the intestine [5], recent studies show that neutrophils are accumulated in colonic mucosa of patients with amebic colitis [6,7] and support that neutrophils play a vital role in resistance to amebic liver abscess and amebic colitis [4,8]. While host immune cells have various mechanisms for eliminating pathogens, E. histolytica has also developed defense strategies for its survival.…”
Section: Introductionmentioning
confidence: 99%